2016
DOI: 10.1038/npp.2016.130
|View full text |Cite
|
Sign up to set email alerts
|

Changes in White Matter Organization in Adolescent Offspring of Schizophrenia Patients

Abstract: Schizophrenia is associated with frontostriatal network impairments underlying clinical and cognitive symptoms. We previously found disruptions in anatomical pathways, including the tract connecting the left nucleus accumbens and left dorsolateral prefrontal cortex (DLPFC). Similar deficits are observed in unaffected siblings of schizophrenia patients, indicating that these deficits are linked to a genetic vulnerability for the disorder. Frontostriatal tract disruptions may arise during adolescence, preceding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Furthermore, our findings are consistent with several studies in UHR samples reporting increased FA compared to healthy controls (Hoptman et al 2008; Bloemen et al 2010; O'Hanlon et al 2015; de Leeuw et al 2017). Specifically, we found that FA was both globally and locally increased and that local WM regions overlap with WM tracts found to be affected in schizophrenia and individuals with 22q11DS and psychosis.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our findings are consistent with several studies in UHR samples reporting increased FA compared to healthy controls (Hoptman et al 2008; Bloemen et al 2010; O'Hanlon et al 2015; de Leeuw et al 2017). Specifically, we found that FA was both globally and locally increased and that local WM regions overlap with WM tracts found to be affected in schizophrenia and individuals with 22q11DS and psychosis.…”
Section: Discussionsupporting
confidence: 93%
“…In the brain, the further development of self-regulation, and thus the rise of strategic control, has been theorized to co-occur with the vast improvement of the quality of connections between cortical and subcortical regions ( Casey et al, 2019 ; Cools, 2011 ; Padmanabhan et al, 2011 ; Vink et al, 2014b ). This is facilitated at the onset of adolescence by the increase in myelination of white-matter tracts connecting these regions ( Asato et al, 2010 ; De Leeuw et al, 2017 ; Ladouceur et al, 2012 ), allowing for faster and more precise neural signalling. Such anatomical changes directly affect brain function and hence behaviours linked to improvements in self-regulation.…”
Section: Development Of Self-regulationmentioning
confidence: 99%
“…In total, 58 SZo (38 families), 94 BDo (60 families), and 56 Co (34 families), aged 8–18 years old, were included between 2010 and 2017. Data at baseline has been partly presented before 33–35 . Figure S1 presents detailed recruitment and drop‐out characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Data at baseline has been partly presented before. [33][34][35] Figure S1 presents detailed recruitment and drop-out characteristics. Overall, 88.5% of the offspring participated at 4-year follow-up: 51 SZo (87.9%), 84 BDo (89.4%), and 49 Co (87.5%).…”
Section: Participants and Proceduresmentioning
confidence: 99%